ADVANTAGES AND DISADVANTAGES OF USING FLIPPED CLASSROOM TO FACILITATE CONCEPT “GLOCAL” IN TERTIARY EDUCATION - Sabadash, Diana; Drechevych, Roksolana; Kakapych, Tetiana; Rudyk, Yulia (Collection of scientific papers «ΛΌГOΣ», 2023)
Globalization processes that dominate in all spheres of life have turned out to be more complex in its nature than it was primarily considered. The focus from polarizing the notions of ‘Local’ and ‘Global’ was shifted to their balanced interrelation, which is reflected by the term ‘Glocal’. The concept “Glocal” has become one of the modern trends in higher education, as it supports its major objectives and principles. Universities as knowledge ecosystems, centers of research and investigation, sources of ideas and innovations for local communities and businesses especially benefit from glocalization and become major actors in its development. Glocal prospects provide necessary means to preserve contact with the local while facing transnational forces; to take local settings, concerns and practices in connection with extra-local ones; to comprehend and respond to the experience of transnational forces; to deal with ecological and social justice; and to provide education capable of producing viable knowledge and practices for global citizenship [8, p. 19-20]. Though the concept of glocalization is widely investigated, the prospects of using flipped classroom methodology to facilitate its implementation within tertiary education has not been studied yet.